A Novel Endothelial Damage Inhibitor Reduces Oxidative Stress and Improves Cellular Integrity in Radial Artery Grafts for Coronary Artery Bypass - Aschacher, Thomas; Baranyi, Ulrike; Aschacher, Olivia; Eichmair, Eva; Messner, Barbara; Zimpfer, Daniel; Moayedifar, Roxana; Laufer, Guenther; Emmert, Maximilian Y.; Sandner, Sigrid E. (Frontiers in Cardiovascular Medicine, 2021)
The radial artery (RA) is a frequently used conduit in coronary artery bypass grafting (CABG). Endothelial injury incurred during graft harvesting promotes oxidative damage, which leads to graft disease and graft failure. We evaluated the protective effect of DuraGraft®, an endothelial damage inhibitor (EDI), on RA grafts. We further compared the protective effect of the EDI between RA grafts and saphenous vein grafts (SVG). Samples of RA (n=10) and SVG (n=13) from 23 patients undergoing CABG were flushed and preserved with either EDI or heparinized Ringer’s lactate solution (RL). The effect of EDI vs. RL on endothelial damage was evaluated ex vivo and in vitro using histological analysis, immunofluorescence staining, Western blot, and scanning electron microscopy. EDI-treated RA grafts showed a significant reduction of endothelial and sub-endothelial damage. Lower level of reactive oxygen species (ROS) after EDI treatment was correlated with a reduction of hypoxic damage (eNOS and Caveolin-1) and significant increase of oxidation-reduction potential. Additionally, an increased expression of TGF, PDGF, and HO-1 which are indicative for vascular protective function were observed after EDI exposure. EDI treatment preserves functionality and integrity of endothelial and intimal cells. Therefore, EDI may have the potential to reduce the occurrence of graft disease and failure in RA grafts in patients undergoing CABG.